Development of an Intelligent System to Monitor the Canal Water Quality and Stagnation Condition - Azim, Akif Rusyaidi; Sim, Sy Yi; Baharom, Md Nor Ramdon (Evolution in Electrical and Electronic Engineering, 2023)
This paper focused on flood and water pollution precaution systems by monitoring the canal system water quality and stagnation condition with a water conductivity probe, hc-sr04 ultrasonic sensor and, sf-y201 water flow sensor. The system will be used to monitor the canal system in Parit Raja, Johor, and send an alert notification when there any abnormalities are detected. The water conductivity probe will measure water conductance. The ultrasonic sensor will measure the water level and the water flow sensor will measure the water flow rate. All of the data will be processed by ESP32 and the data can be presented through the Arduino IoT dashboard The system is tested with various tests to verify its validity. The reading from the water conductivity probe and ultrasonic sensor will be compared with an actual reading, while the water flow test will be tested with the presence of water flow in the canal system. The notification feature will be tested by manipulating the parameter conditions. For water conductivity, the percentage error shows that the system reading is fairly accurate while the water level reading is accurate. For the water flow rate, flow rate can be noticed through the Arduino IoT dashboard. Finally, the notification was sent to the IoT dashboard when manipulating the parameters condition. Overall, the proposed system is successful to monitor the water quality and stagnation conditions.